2015
DOI: 10.1002/ep.12188
|View full text |Cite
|
Sign up to set email alerts
|

Impact of local conditions on bio‐based chemical process design: selection of input feedstock and production scale and scenario

Abstract: Economic incentive is an important driving force for the implementation of bio‐based chemical industry. The economic performance of a bio‐based chemical process is influenced strongly by the input biomass feedstock and production scale and scenario that must be selected with respect to the local conditions, such as the availability, distribution, and transportation distance of biomass feedstocks, which differ according to regional productivity, regional production scale, and geographical distribution of biomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Connecting the identified drivers of the STEEPLE analysis of the 21 international bioeconomy peer-reviewed scientific studies, project reports, and scenario studies [2,8,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] and of the narrative analysis, shows that, at the minimum, in one study, at least two drivers could be found (see Figure 2). Based on this assessment, it can be stated that the identified drivers from the strategy are also those used in present scientific discourse.…”
Section: Assessed Drivers Of a Future German Bioeconomymentioning
confidence: 99%
“…Connecting the identified drivers of the STEEPLE analysis of the 21 international bioeconomy peer-reviewed scientific studies, project reports, and scenario studies [2,8,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] and of the narrative analysis, shows that, at the minimum, in one study, at least two drivers could be found (see Figure 2). Based on this assessment, it can be stated that the identified drivers from the strategy are also those used in present scientific discourse.…”
Section: Assessed Drivers Of a Future German Bioeconomymentioning
confidence: 99%